Puentes, carreteras y transporte terrestre como causas de impactos medioambientales negativos en la selva baja peruana - Junquera Rubio, Carlos (M+A. Revista Electrónica de Medioambiente, 2007)
The Amazon region through which the Interoceanic road will pass is the most pristine area of Peruvian forest and one of the greatest concentrations of biodiversity on the planet, including a high number of endemic species, due to its good state of general conservation and the enormous variety of ecosystems. In the region there exists a passive environmental and social significance that comes from the impacts produced gradually and cumulatively by the construction, in the 1940s and 1950s, of penetration roads in the Amazon region from Cuzco and Puno. The most probable environmental impacts, seen over a ten year period, include increased deforestation, degrading of tropical forest, the invasion of protected areas, a greater incidence of forest fires, the expansion of illegal crops, the anarchic exploitation of gold, and increased hunting and fishing.